Contemporary Treatment of Crime Victims/Survivors: Barriers Faced by Minority Groups in Accessing and Utilizing Domestic Abuse Services - Terri Cole; Orlanda Harvey; Jane C. Healy; Chloe Smith (Behavioral Sciences)
This research explored the experiences of LGBTQIA+, black and ethnic minority (BME), and disabled victims of domestic abuse due to the frequency of abuse in these populations and bespoke needs they may have. Data were collected via an online survey (n = 317), a focus group with professionals (n = 2), and interviews with victims/survivors of domestic abuse (n = 2). Many victims/survivors articulated difficulties in accessing support for many reasons, including individual and structural barriers such as embarrassment, stigma, shame, fear and not being aware of what support is available. Whilst good practice was reported, examples of secondary victimization towards victims/survivors by individuals, professionals and organizations were recounted. Many barriers were identified; for example, there was inappropriate provision in refuges or shelters for LGBTQIA+ groups or disabled people. Disabled victims experienced additional barriers if their abuser was also their carer. BME groups may have additional language difficulties as well as cultural stigma and pressure to stay with their abuser. Recommendations for practice include the need for enhanced multi-agency training and recognition of abuse; crime against victims/survivors being supported by someone with the same cultural background; easier access to interpreters; and more appropriate refuge or alternative housing options.